Phylogenetic reconstruction based on COI reshuffles the taxonomy of hyalosphenid shelled (testate) amoebae and reveals the convoluted evolution of shell plate shapes. (17th July 2016) - Kosakyan, Anush; Lahr, Daniel J. G.; Mulot, Matthieu; Meisterfeld, Ralf; Mitchell, Edward A. D.; Lara, Enrique
Abstract: Species diversity in most protistan groups has been underestimated. Many morpho‐species are in fact complexes that require detailed morphometric studies to be discriminated. However, which traits can be used for species descriptions remains in many cases unclear. The testate amoeba genus Quadrulella produces self‐secreted, siliceous plates with a very characteristic square shape—such plates were assumed to be synapomorphic of the genus. Here we demonstrate that Quadrulella symmetrica (the most common Holarctic species) is not monophyletic. Square plate size and arrangement, test size and general shape are efficient criteria for species discrimination. Based on morphology and sequence data, we describe Quadrulella variabilis sp. nov. from Switzerland, and Quadrulella madibai sp. nov. from South Africa, and confirm the validity of Q. alata . The former species Q. subcarinata does not belong to the genus Quadrulella . We therefore transfer this species to the new genus Mrabella gen. nov. Our results show that hyalosphenids presenting siliceous square shell plates do not form a monophyletic clade. Several possible hypotheses about the origins of square plates are discussed. Additionally, this comprehensive phylogenetic analysis of the family Hyalospheniidae confirms that the genus Nebela is paraphyletic and needs to be divided into genera based on general shell shape: Nebela sensu stricto, Longinebela gen. nov., Planocarina gen. nov., Gibbocarina gen. nov., Cornutheca gen. nov. and Mrabella gen. nov.